Analisis Konseptual Peran Pemuda dalam Pembangunan Desa Berdasarkan Undang-Undang Desa - Fatori, Ach; Fatimah, Haliza; Marseli Faderi, Lannie (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This study aims to conceptually analyze the role of youth in village development based on the regulatory framework of Law Number 3 of 2024 on Villages, as well as to identify the challenges and opportunities associated with it. The research employs a qualitative approach using literature review methods, drawing from scholarly journals, books, and relevant policy documents. The findings indicate that the main barriers to youth participation include entrenched seniority culture, limited access to resources, minimal involvement in decision-making processes, and a persistent trend of urban migration. Nevertheless, three key opportunities can be optimized: youth involvement in village development planning, the promotion of local youth entrepreneurship, and the digital transformation of villages. Strengthening the role of youth requires a supportive ecosystem encompassing affirmative policies, capacity-building programs, institutional support, and access to funding. Through collaborative and regulatory approaches, youth can serve as a driving force for inclusive, self-reliant, and sustainable village development.